Persepsi Siswa SMA Negeri 1 Sirah Pulau Padang Terhadap Cyberbullying di Jejaring Sosial Facebook - Susanti, Devi; Jannati, Zhila; Razzaq, Abdur (Bulletin of Counseling and Psychotherapy, 2019)
Ethics and morals are one of the most important parts that must be understood by users of Facebook which serve as guidelines for behavior of Facebook users to avoid the occurrence of cyberbullying. The purpose of this study is to determine the perception of High School 1 Sirah Pulau Padang towards cyberbullying on Facebook. The method used in this study is a qualitative research. The data collection techniques used in this study were interview, observation, and documentation. The results of this study are: 1) Students of High School 1 Sirah Pulau Padang on average already have a facebook account, 2) Perception of students of High School Negeri 1 Sirah Pulau Padang regarding cyberbullying as acts of violence or crimes on social media such as mutual ridicule and bullying each other on social media, 3) Students' perceptions of the most common forms of cyberbullying are Flaming and Harassment, 4) Perception of students of High School 1 Sirah Pulau Padang regarding the causes of perpetrators of cyberbullying namely because of revenge, fun or joking with their friends , and the feeling of disappointment or hurt from the perpetrator, 5) Students' perceptions of the impact of cyberbullying behavior, namely victims of cyberbullying feel aggrieved, disappointed, sad and lead to fights between students, and 6) Students' perceptions of appropriate penalties for cyberbullying, namely accounts Facebook from cyberbullying perpetrators is frozen until it can be followed up to the legal domain.